RURAL POPULATION AND POVERTY - Jelić, Sreten; Jovanović, Tatjana (Economics of Agriculture, 2011)
In the first part of paper we have tried to point out some social and demographic determinants of population structure and characteristics of the population in rural areas. Rural population have significant role, not only in development of agriculture but also other activities in rural areas. Structure of rural population is significantly changed. The second part discusses the phenomenon of poverty facing the population, households and farms. The analysis included some indicators pointing the poverty.